INTEGRASI STEAM DALAM PEMBELAJARAN IPA MATERI BUNYI UNTUK MENGEMBANGKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Intan Arini; Nuraini; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the importance of developing elementary school students’ science process skills in science education. The integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) is one approach that can support the development of these skills. The focus of this study is on how STEAM-based science education using sound-related materials can enhance elementary school students’ science process skills. This study employs a quantitative approach and utilizes a quasi-experimental design. It was conducted using a one-group pretest-posttest design. The subjects of the study were 30 fifth-grade students at a public elementary school in Pekanbaru, selected through purposive sampling. Data were collected using a science process skills test, observation sheets, and documentation. Data were analyzed descriptively by comparing students’ pre- and post-test results. The results showed that students had an average pre-test score of 66, while their average post-test score was 64. STEAM-based learning provided a more active learning experience through observation, experimentation, and the creation of simple musical instruments, despite a 2% decrease in scores. Students learned various science process skills, such as observing, classifying, predicting, conducting experiments, and communicating observation results through these activities. Therefore, the integration of STEAM into science education enables contextual learning experiences and can support the development of science process skills among elementary school students.